Associations of microbial and indoleamine-2,3-dioxygenase-derived tryptophan metabolites with immune activation in healthy adults - Riazati, Niknaz; Kable, Mary E.; Newman, John W.; Adkins, Yuriko; Freytag, Tammy; Jiang, Xiaowen; Stephensen, Charles B. (Frontiers in Immunology, 2022)
Background Tryptophan (Trp) metabolites from intestinal bacteria (indole, indole acetic acid [IAA] and indole propionic acid [IPA]), and the Trp metabolite kynurenine (Kyn) from the indoleamine 2,3-dioxygenase (IDO) pathway, are aryl hydrocarbon receptor (AhR) agonists and thus, can regulate immune activity via the AhR pathway. We hypothesized that plasma concentrations of these metabolites would be associated with markers of immune activation in a cohort of healthy adults in a manner consistent with AhR-mediated immune-regulation. We also hypothesized that the plasma Kyn/Trp ratio, a marker of IDO activity, would be associated with immune markers reflecting IDO activation in innate immune cells. Finally, we hypothesized that some intestinal bacteria would be associated with plasma indole, IPA or IAA, and that these bacteria would themselves be associated with immune markers. Methods A novel set of 88 immune markers, and plasma Trp metabolites, were measured in 362 healthy adults. Bacterial taxa from stool were identified by 16S rRNA gene analysis. Multiple linear regression analysis was used to identify associations with immune markers. Results The sum of indole and IAA was positively associated with natural killer T-cells levels. Kyn and Kyn/Trp were positively associated with neopterin and IP-10, markers of type 1 immunity, and TNF-α and C-reactive protein (CRP), markers of the acute phase response, and the regulatory cytokine IL-10. Three bacteria negatively associated with Trp metabolites were associated with markers of immune activation: the family Lachnospiraceae with higher lymphocyte counts but lower level of activated CD4 T-cells, the genus Dorea with higher production of IFN-γ by T-cells in PBMC cultures, and the genus Ruminococcus with higher production IL-6 in PBMC cultures stimulated with bacterial lipopolysaccharide. Conclusions In this cohort of healthy adults bacterial Trp metabolites were not strongly associated with immune markers. Conversely, the Kyn/Trp ratio was strongly associated with markers of systemic inflammation and the acute phase response, consistent with IDO activation in innate immune cells. Finally, commensal bacteria associated with lower plasma (and perhaps intestinal) levels of bacterial Trp metabolites were associated with greater immune activation, possibly reflecting decreased regulatory immune activity related to lower intestinal levels of bacterial indole metabolites.